PENGARUH STRATEGI KWL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 9 AMPENAN TAHUN AJARAN 2019/2020 - Fitmi Kayanti; Muhammad Tahir; Syaiful Musaddat (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
The purpose of this study was to looking for the effect of KWL Strategy (Know - Want To Know - Learned) towards students' reading comprehension in fourth grade of SDN 9 Ampenan. The population was all of the students in fourth grade as much 107 students, as the result this study was carried out in two classes i.e. IVA as the experiment class and IVB as the control class and the sample was choosen using purposive sampling, techniques particually Nonequivalent control group design,. Based on the title, this study consisted of independent and dependent variable where KWL Strategy as the independent variable while students' reading comprehension as the dependent variable. The data that already collected was analyzed using covariance analysis (anacova) and as the result, it showed that there is significant effect of KWL strategy (Know- Want to Know- Learned) towards the students' reading comprehension with a value of Fobserved > Ftable, which is 5.068 > 3.98.